2020
DOI: 10.2147/cia.s243902
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Cytoreductive Partial Nephrectomy in Elderly Patients with Metastatic Renal Cell Carcinoma</p>

Abstract: Objective: To explore the survival value of cytoreductive partial nephrectomy (cPN) in elderly with metastatic renal cell carcinoma (EmRCC) and evaluate the characteristics of patients who benefit from cPN. Materials and Methods: This was a study including 6105 patients aged ≥65 years with metastatic renal cell carcinoma (RCC) queried from Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2015, among which 1264 patients underwent cytoreductive nephrectomy (CN), 78 patients underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Nomogram is a data-based graphical computing tool that can estimate the risk of developing a disease based on staging systems, such as the American Joint Commission on Cancer (AJCC) and other key risk factors related to prognosis ( 42 ). Today, many kinds of nomograms have been developed and applied to RCC, such as Chen et al ( 43 ), who included 6,105 elderly patients with metastatic RCC in the SEER database from 2010 to 2015, indicating the advantages of PN in elderly mRCC. Michele et al ( 44 ) included 4,541 patients with RCC over 75 years of age in the SEER database from 2004 to 2014 and proved that PN did not increase the mortality of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram is a data-based graphical computing tool that can estimate the risk of developing a disease based on staging systems, such as the American Joint Commission on Cancer (AJCC) and other key risk factors related to prognosis ( 42 ). Today, many kinds of nomograms have been developed and applied to RCC, such as Chen et al ( 43 ), who included 6,105 elderly patients with metastatic RCC in the SEER database from 2010 to 2015, indicating the advantages of PN in elderly mRCC. Michele et al ( 44 ) included 4,541 patients with RCC over 75 years of age in the SEER database from 2004 to 2014 and proved that PN did not increase the mortality of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, when they stratified the data by tumor size, they found this benefit to be isolated to small renal tumors (less than 4 cm). Chen et al 13 also showed survival advantage of patient who underwent cPN versus cRN. After subgroup analysis they also confirmed that OS was superior only in male patients with ⩽7 cm tumor, N0 and isolated metastasis and even in the N1 stage, cPN results was worse than cRN.…”
Section: Table 2 Quality Assessment Items and Possible Scoresmentioning
confidence: 92%
“…Data from the SEER database and the National Cancer Database (NCDB) show a PN rate of 4.2% and 3.8%, respectively [82,83]. PN did not show inferior oncological outcomes compared to radical nephrectomy (RN) in four studies [82,[84][85][86] and was, on the contrary, associated with better outcomes in three published sets [9,82,87]. The rate of early (30 days) complications in PN in solitary kidneys was higher compared to RN (33% vs. 10%, p = 0.009) [86].…”
Section: Surgical Aspects Of Cytoreductive Nephrectomymentioning
confidence: 94%